Efficient implementations of expressive modelling languages - Chupin, Guerric (2022)
This thesis is concerned with modelling languages aimed at assisting with modelling and simulation of systems described in terms of differential equations. These languages can be split into two classes: causal languages, where models are expressed using directed equations; and non-causal languages, where models are expressed using undirected equations.